Pregnancy at very advanced maternal age: a UK population‐based cohort study. (1st September 2016) - Fitzpatrick, KE; Tuffnell, D; Kurinczuk, JJ; Knight, M
Abstract : Objectives: To describe the characteristics, management and outcomes of women giving birth at advanced maternal age (≥48 years). Design: Population‐based cohort study using the UK Obstetric Surveillance System (UKOSS). Setting: All UK hospitals with obstetrician‐led maternity units. Population: Women delivering at advanced maternal age (≥48 years) in the UK between July 2013 and June 2014 ( n  = 233) and 454 comparison women. Methods: Cohort and comparison group identification through the UKOSS monthly mailing. Main outcome measures: Pregnancy complications. Results: Older women were more likely than comparison women to be overweight (33% versus 23%, P  = 0.0011) or obese (23% versus 19%, P  = 0.0318), nulliparous (53% versus 44%, P  = 0.0299), have pre‐existing medical conditions (44% versus 28%, P  < 0.0001), a multiple pregnancy (18% versus 2%, P  < 0.0001), and conceived following assisted conception (78% versus 4%, P  < 0.0001). Older women appeared more likely than comparison women to have pregnancy complications including gestational hypertensive disorders, gestational diabetes, postpartum haemorrhage, caesarean delivery, iatrogenic and spontaneous preterm delivery on univariable analysis and after adjustment for demographic and medical factors. However, adjustment for multiple pregnancy or use of assisted conception attenuated most effects, with significant associations remaining only with gestational diabetes (adjusted odds ratio [aOR] 4.81, 95% CI 1.93–12.00), caesarean delivery (aOR 2.78, 95% CI 1.44–5.37) and admission to an intensive care unit (aOR 33.53, 95% CI 2.73–412.24). Conclusions: Women giving birth at advanced maternal age have higher risks of a range of pregnancy complications. Many of the increased risks appear to be explained by multiple pregnancy or use of assisted conception. Tweetable abstract: The pregnancy complications in women giving birth aged 48 or over are mostly explained by multiple pregnancy. Tweetable abstract: The pregnancy complications in women giving birth aged 48 or over are mostly explained by multiple pregnancy.